Exploring Challenges and Coping Strategies in Using Non Technology Based Teaching Media and Materials at Sman 2 Ranah Pesisir - Rahmawanti, Indah; Mairi, Salam (Universitas Negeri Padang, 2025)
This study explores the challenges and strategies used by teachers in teaching English without technology. The research was conducted at SMAN 2 Ranah Pesisir, a rural public high school with limited access to digital tools in classrooms. Although the school has facilities such as computers and projectors, they are not commonly used for instructional purposes. This condition leads teachers to rely on conventional media and teaching methods. Using a qualitative method with a case study approach, this study involved three teachers: one English teacher as the main subject and two other subject teachers as supporting participants. Data were collected through semi-structured interviews and analyzed using an interactive process involving data condensation, display, and conclusion drawing. The findings show that teachers used non-technological media such as whiteboards, printed books, flashcards, and contextual examples. The main challenges included limited media variety, low student motivation, and minimal digital support. To address these challenges, teachers applied creative strategies such as personalized learning, emotional connection, storytelling, and group discussion to maintain student engagement. The study concludes that effective English teaching is achievable in low-technology settings when teachers apply strong pedagogical knowledge, adapt to their context, and implement suitable strategies.